Legal Uncertainty Regarding the Status of Children Born Out of Wedlock in the Perspective of Hifdzu al-Nasl - Husien, Syarief (Unissula, 2024)
The concept of hifzu al-nasl in maqasid sharia emphasizes the importance of protecting one's nasab, providing legal protection, and fulfilling children's rights to achieve a prosperous life in this world and the hereafter. The aim of the resulting research is to analyze the concept of hifdzu al-nasl in maqasid as-syariah in legal certainty regarding the status of children outside of marriage. This research uses a doctrinal research approach. In the context of hifzu al-nasl, the principles of maqasid as-syariah emphasize the need to protect the nasab, uphold the rights of children, and guarantee the welfare of descendants to achieve justice in this world and the hereafter. The novelty of this research highlights the importance of an integrative approach between positive law and Islamic law to overcome legal uncertainty surrounding illegitimate children, as well as expanding the meaning of hifzu al-nasl by including recognition of children's rights without linking them directly to biological birth.